Whole-process crack width prediction of reinforced concrete structures considering bonding deterioration. (1st July 2017) - Xu, Li-Yan; Nie, Xin; Zhou, Meng; Tao, Mu-Xuan
Highlights: A fiber beam-column model for the whole-process crack width prediction of reinforced concrete structures is proposed. The reinforced concrete member is partitioned into the cracking, bonding, and deterioration regions for analysis. The concept of the "deterioration region" is introduced to consider the gradual failure of bonding interface. The quarter-ellipse curve is used to describe the tension softening effect of cracking concrete. Simulations of crack width, crack distribution, crack evolution, and crack-loading response for RC structures are presented. Abstract: Monitoring the crack width of reinforced concrete (RC) structures is essential to assess their damage and durability. However, traditional methods of crack calculation are confined to the formulas for predicting the crack width in a single RC member at the service limit state. In this paper, based on the theoretical analysis of microscopic interface between concrete and rebar, an approach for the whole-process crack width prediction is proposed to trace the crack evolution of overall RC structures when subjected to cyclic loading such as earthquakes. To describe the tensile behavior characterized by the tension stiffening and tension softening effects, a modified model considering the bonding deterioration—dubbed here as the "β-ellipse model" —is formulated as an extension of conventional model based on bond-slip interaction. Then, by implementing the β -ellipse model in the framework of the fiber beam-column element model, the approach for calculating and displaying the crack width in finite element analysis (FEA) is presented. Finally, the accuracy of the developed fiber model is verified by comparing the simulated performance with extensive test results of RC members. The comparisons indicate that the model can elaborately simulate the crack width, crack distribution, crack evolution, and crack-load response of both the single cracking section and overall component, which offers a reliable and efficient tool for the whole-process crack width prediction in nonlinear FEA of RC structures.